The Effect Of Corporate Governance and the Quality of CSR to Tax Avoidation - Apriliyana, Nining -; Suryarini, Trisni (Accounting Analysis Journal, 2018)
The purpose of this research was to analyse the effect of Corporate Governance and Corporate Social Responsibility Quality on tax avoidance. The population used in this research was 150 manufacturing company listed in the Indonesia Stock Exchange during 2013-2015. The technique used for get sampling is purposive sampling, with the resulting in a final sample of 29 manufacturing companies. The analytical tools used to test the hypothesis are descriptive statistical analysis and multiple regression analysis were processed with IBM SPSS 21. The result of this research of institutional ownership and CSR quality have no effect on companies tax avoidance. Nevertheless, an executive compensation has a positive effect on companies tax avoidance. The background in accounting or financial expertise of audit committee negatively affects tax avoidance in the manufacturing company during 2013-2015. The conclusions of this study is that executive compensation and background accounting or financial expertise of audit committee can significantly influence in tax avoidance decisions. Meanwhile, institutional ownership and CSR quality have no significant effect in tax avoidance decisions on manufacturing companies listed on Indonesia Stock Exchange during 2013-2015.